Effect of Earning Asset Quality, Financial Leverage, and Company Size on Financial Performance of Sharia Commercial Banks - Inayatul Maula; Tiara Juliana Jaya (Universitas Muhammadiyah Surabaya, 2022)
The research aims to see earning asset quality, financial leverage, and company size influence the financial performance of Islamic Commercial Banks from 2016 and 2020. A descriptive quantitative statistical technique is used in this type of research. With Eviews software version 10, the data was used as panel data with analysis capabilities in the form of panel data regression. The study employed a purposive sampling technique to select a sample of 10 Islamic commercial banks registered with the OJK. Purposive sampling was performed since the researchers have specific criteria. The research found that concurrently had a substantial impact on Islamic commercial banks' financial performance. However, the partial test results reveal that the quality of earning assets and company size have such a considerable negative impact on Islamic commercial banks' financial performance, but financial leverage has no impact on financial performance.